Efficacy of low dose hyperbaric bupivacaine in spinal anaesthesia for LUCS (Bangladesh Medical Journal Khulna, 2013)
Spinal Anaesthesia (SAB) is a popular anaesthetic technique in LUCS. SAB is performed in sitting and lateral position. The aim of this study is to explore the efficacy of spinal anaesthesia ie, height of block and haemodynamic changes with low dose hyperbaric bupivacaine in different position in LUCS. Total 80 of ASA grade I & II elective LUCS patient preloaded with 800-1000 ml of isotonic fluid were allocated randomly to receive different doses (10 mg, 12 mg,) of 5% Hyperbaric bupivacaine at L4-L5 interspaces in sitting (S group) and in lateral (L group) position to compare the height of block and haemodynamic changes. In sitting position in 10 mg dose group (S 10) adequate block developed in 7 patients out of 20 (35%) with no fall of systolic BP, in 12 mg dose group (S12) adequate block developed in 14 patients out of 20 (70%) with fall of systolic BP>1/3rd in 2 patients (10%). In lateral position groups (L group) with 10 mg dose ((L 10 group), 17 patients out of 20 got adequate block (85%) with fall of systolic BP>1/3rd in 2 patients out of 20 (10%) and in 12 mg dose group (L 12) adequate block in 20 patients out of 20 (100%) with fall of systolic BP>1/3rd in 5 patients out of 20 (25%). So block height with low dose of Hyperbaric Bupivacaine for caesarean section is more predictable and haemodynamically stable in lateral position DOI: http://dx.doi.org/10.3329/bmjk.v45i1-2.13624 Bang Med J (Khulna) 2012; 45 : 15-18